Comparison of bone microstructures via high-resolution peripheral quantitative computed tomography in patients with different stages of chronic kidney disease before and after starting hemodialysis. Issue 1 (31st December 2022) - Tsuji, Kiyokazu; Kitamura, Mineaki; Chiba, Ko; Muta, Kumiko; Yokota, Kazuaki; Okazaki, Narihiro; Osaki, Makoto; Mukae, Hiroshi; Nishino, Tomoya
Abstract: Chronic kidney disease (CKD) negatively affects bone strength; however, the osteoporotic conditions in patients with CKD are not fully understood. Moreover, the changes in bone microstructure between pre-dialysis and dialysis are unknown. High-resolution peripheral quantitative computed tomography (HR-pQCT) reveals the three-dimensional microstructures of the bone. We aimed to evaluate bone microstructures in patients with different stages of CKD. This study included 119 healthy men and 40 men admitted to Nagasaki University Hospital for inpatient education or the initiation of hemodialysis. The distal radius and tibia were scanned with HR-pQCT. Patient clinical characteristics and bone microstructures were evaluated within 3 months of initiation of hemodialysis (in patients with CKD stage 5 D), patients with CKD stage 4–5, and healthy volunteers. Cortical bone parameters were lower in the CKD group than in healthy controls. Tibial cortical and trabecular bone parameters (cortical thickness, cortical area, trabecular volumetric bone mineral density, trabecular-bone volume fraction, and trabecular thickness) differed between patients with CKD stage 5 D and those with CKD stage 4–5 ( p  < 0.01). These differences were also observed between patients with CKD stage 5 and those with CKD stage 5 D ( p  < 0.017), but not between patients with CKD stage 4 and those with CKD stage 5, suggesting that the bone microstructure rapidly changed at the start of hemodialysis. Patients with CKD stage 5 D exhibited tibial microstructural impairment compared with those with CKD stage 4–5. HR-pQCT is useful for elucidation of the pathology of bone microstructures in patients with renal failure.